Resolution of Complex Refractory Autoimmune Hemolytic Anemia in Pregnancy after Five Lines of Therapy-True Multidisciplinary Approach - PADMAJA, LOKIREDDY; Ranganathan, Dr. Sudha; Khammammettu, saketh; Nagapuri, Dr. Sandeep; Shaik, Ameena (International Journal of Innovative Research in Medical Science, 2024)
Autoimmune hemolytic anemia (AIHA) is a condition where the body's immune system destroys its own red blood cells, leading to symptoms such as fatigue, pallor, jaundice, and shortness of breath. AIHA presents a complex clinical challenge during pregnancy [1]. There is paucity of information on management of complex cases of steroid refractory AIHA. Here, we discuss a unique case of a 24-year-old primigravida who presented with anemia and jaundice at 6 weeks of gestation. Sequential therapies including steroids, IVIG, Rituximab, Cyclophosphamide, and plasma exchange proved refractory. A peri-partum splenectomy performed simultaneously with an early cesarean section at 32 weeks’ gestation resulted in resolution of this patient's AIHA.